2022
DOI: 10.3390/diagnostics12081810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nasal Foreign Bodies in South Korea: Over 10-Year Experience

Abstract: Foreign bodies (FBs) in the nasal cavity are commonly encountered in otorhinolaryngology. This retrospective study was conducted between January 2009 and December 2020. The nasal FB frequencies were investigated according to age and sex. The type, shape, and location of the FBs, onset, and clinical features were obtained. In a total of 1228 cases, the average age was 3.9 ± 5.7 years. We found a higher incidence in patients 2–4 years old. The most frequent nasal FBs were beads (24.0%), toys/plastics (17.8%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A previous study on 87 children by Aslan et al found that 42.5% were of the female gender [ 7 ]. Though in the majority of cases (62.1-71%), the foreign body was found to be organic in nature [ 7 , 8 ], the round-shaped foreign bodies, whether organic or inorganic, are the most commonly found inserted in the nasal cavities by children [ 9 ]. Our patient inserted a spade-shaped foreign body, which has round borders, making it easier to insert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on 87 children by Aslan et al found that 42.5% were of the female gender [ 7 ]. Though in the majority of cases (62.1-71%), the foreign body was found to be organic in nature [ 7 , 8 ], the round-shaped foreign bodies, whether organic or inorganic, are the most commonly found inserted in the nasal cavities by children [ 9 ]. Our patient inserted a spade-shaped foreign body, which has round borders, making it easier to insert.…”
Section: Discussionmentioning
confidence: 99%
“…They may insert objects into their nostrils as a form of entertainment, experimentation, or imitation. Little objects, such as beads, food, or little toys, are popular alternatives for children to investigate [ 6 , 9 , 12 ]. This is similar to our patient who inserted a necklace bead, highlighting the need for extra vigilance for her parent, who reported seeing her inserting something.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal foreign bodies are commonly encountered in the emergency department and require prompt intervention to avoid the onset and progression of complications. Foreign bodies in the nasal cavity are frequently reported in children but may also be encountered in adults with mental disorders or nasal trauma[ 1 , 2 ]. Adult patients often lack awareness of nasal ectopia, which delays treatment.…”
Section: Introductionmentioning
confidence: 99%